An Analysis of Students’ Anxiety in Learning English At The Fourth Semester Students of Midwifery Department in Aufa Royhan University: Analysis of Students’ Anxiety in Learning English At The Fourth Semester Students of Midwifery Department in Aufa Royhan University - handayani, fitri rahma; nurdin, hidayanti rohimah; Juliana, Juliana; siregar, Sarmila hafni; Nasution, Nurlaila (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
English is the most widely used language in the world. As a result, it is crucial for students to learn English. To do it, someone must not have anxiety towards it. word "anxiety" refers to a state of fear, worry, or trepidation. It is a significant factor that influences how students learn in the classroom. The purpose of the study was to would like to analyse the students’ anxiety in learning English at the fourth semester students of midwifery department in Aufa Royhan university. The researcher used descriptive research studies to gather information about the current state of phenomena. The data collection instrument was a questionnaire to gather information from respondents about their interest towards English. The results showed that the internal factor indicators were motivation, lack of self-assurance, fear of making mistakes, reticence. The external factor indicators were a lack of vocabulary, grammar mistakes, friends or classmates, embarrassment, and lack of preparation. The overall result showed that students still had anxiety in learning English. So, they must improve their motivation especially towards English to help them have good achievements both in school or work later. Keywords: Anxiety, English, Students